2014
DOI: 10.1155/2014/930907
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Proliferation and Differentiation Potentials of Stem Cells from Inflamed Pulp of Deciduous Teeth and Stem Cells from Exfoliated Deciduous Teeth

Abstract: Stem cells isolated from exfoliated deciduous teeth (SHEDs) are highly capable of proliferation and differentiation, and they represent good cell sources for mesenchymal stem cell- (MSC-) mediated dental tissue regeneration, but the supply of SHEDs is limited. A previous study found that stem cells could be isolated from inflamed tissues, but it is unknown whether primary dental pulp diagnosed with irreversible pulpitis might contain stem cells with appropriate tissue regeneration capacity. In this study, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…In addition to the effects of DSPP mutation, the pathological condition of dental pulp may influence the changes of pulp cells; therefore, DGI cells’ characteristics should be interpreted with caution. Cells isolated from inflamed dental pulp tissues were previously shown to have changes in inflammatory mediators such as tumour necrotic factor α and toll‐like receptors (Fawzy El‐Sayed, Klingebiel, & Dörfer, ; Yu et al., ). Nonetheless, several studies demonstrated no significant differences in cellular behaviours including surface marker expression, proliferation, and differentiation abilities of the cells isolated from inflamed and healthy pulp tissues of both primary and permanent teeth (Böttcher, Scarparo, Batista, Fossati, & Grecca, ; Lee, Zhang, Karabucak, & Le, ; Tandon, Saha, Rajendran, & Nayak, ; Yu et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effects of DSPP mutation, the pathological condition of dental pulp may influence the changes of pulp cells; therefore, DGI cells’ characteristics should be interpreted with caution. Cells isolated from inflamed dental pulp tissues were previously shown to have changes in inflammatory mediators such as tumour necrotic factor α and toll‐like receptors (Fawzy El‐Sayed, Klingebiel, & Dörfer, ; Yu et al., ). Nonetheless, several studies demonstrated no significant differences in cellular behaviours including surface marker expression, proliferation, and differentiation abilities of the cells isolated from inflamed and healthy pulp tissues of both primary and permanent teeth (Böttcher, Scarparo, Batista, Fossati, & Grecca, ; Lee, Zhang, Karabucak, & Le, ; Tandon, Saha, Rajendran, & Nayak, ; Yu et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The hSHEDs were first isolated by Miura et al and are highly proliferative-clonogenic multipotent cells that have the potential of differentiating to functional osteoblasts, odontoblasts, chondroblasts, adipocytes, neural cells, and endothelial cells both in vitro and in vivo (4,5,(11)(12)(13)(14). The broad differentiation and proliferation capacity of hSHEDS makes these cells a good potential source for treatments of craniofacial defects and tooth loss and may also be used for bone regeneration (15).…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of these cells is mainly based on the severity of inflammation namely in regard to reversible and irreversible pulpitis. For instance, a study described such cells as having a reduced competency compared to healthy samples in their in vitro proliferation as well as multidifferentiation capabilities (Kim et al 2014), whilst another reported no significant differences when using stem cells from either inflamed or healthy pulps (DPSCs-RP and DPSCs, respectively) (Yu et al 2014). Despite this limita-Correspondence: Vijayendran Govindasamy, GMP-compliant stem cells laboratory, Hygieia Innovation Sdn.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies on inflamed pulp cells focus mainly on basic proliferation rates, differentiation capacities especially towards chondrogenesis, osteogenesis and adipogenesis, and immunomodulatory effects, although results have been generally inconsistent (Kim et al 2014, Yazid et al 2014. For instance, a study described such cells as having a reduced competency compared to healthy samples in their in vitro proliferation as well as multidifferentiation capabilities (Kim et al 2014), whilst another reported no significant differences when using stem cells from either inflamed or healthy pulps (DPSCs-RP and DPSCs, respectively) (Yu et al 2014).…”
Section: Introductionmentioning
confidence: 99%